Mechanical Pruning of Citrus Trees - Mongi Zekri (EDIS)
When citrus trees are not regularly pruned, less sunlight reaches the lower parts of the trees, which can reduce flowering and fruit development, quality, and color. Less sunlight also increases the risk of fungal infection. This 3-page fact sheets explains how growers can prune trees to maximize light exposure. Written by Mongi Zekri, and published by the UF Department of Horticultural Sciences, August 2015.